Adventitious Plantlet Formation In Bambusa tulda – A New Report - BORAH, ELLORA DUTTA; HAZARIKA, PRODIP KR.; PRADHAN, BIJOY; JAYARAJ, R.S.C. (Indian Forester, 2023)
The paper documents an unusualÂ formation of above ground rhizome in the culms of Bambusa tulda, effectively serving as an adventitious plantlet. From the survey ofÂ review of literature, it is found that there is no report on formation ofÂ adventitious plantlet in B. tulda andÂ this seems to be the new report .